(untitled) (World Bulletin of Public Health, 2024)
Currently, the most commonly used criterion for the hemodynamic significance of PD is the maximum LSC in the focus of deformation, however, the authors’ opinions on the critical value of LSC, above which PD can be considered hemodynamically significant, differ. Thus, some authors cite specific values of LSC at the bending height, which vary in a wide range of values: from 100 cm/s to 240 cm/s, while other researchers take an increase in LSC in the knee of tortuosity at the inner radius more than 2 times from the values determined before it as a criterion of hemodynamic significance, and there is also a turbulent blood flow in the tortuosity area. Some scientists draw an analogy between deformity and atherosclerotic stenosis of the carotid artery and measure the degree of narrowing as a percentage. Quantitative assessment of the reactivity of the brain is carried out on the basis of special tests, one of the most common is hypercapnic. The results of work on the study of the functional state of the cerebral circulation reserve in patients with PD ICA converge in a decrease in reactivity in this category of patients, but we did not find a comparison of the indicators of the cerebral circulation reserve with the structure of the Willis circle, the form of deformation, the degree of cerebrovascular insufficiency and indicators of blood flow at the bend in this category of patients in the studies presented in the literature. Based on the above, we see that the concept of "hemodynamic significance" of PD is very vague. The data from various surgical schools are extremely contradictory and are based on a variety of criteria that are not unified.